Association between the age-related decline in renal function and lumbar spine bone mineral density in healthy Chinese postmenopausal women. Issue 5 (May 2018) - Han, Wen; Bai, Xiao-Juan; Han, Lu-Lu; Akhtari, Sebastian; Sun, Xue-Feng; Chen, Xiang-Mei
Abstract: Objectives: The relationship between the decline of renal function and bone mineral density (BMD) in healthy populations is not well-researched. The aim of this study was to investigate the association between the age-related decline in renal function and lumbar spine BMD (LBMD) in a community-based cross-sectional study of 390 healthy postmenopausal women (mean age 62.97 ± 8.79 years) from Shenyang, China. Methods: Dual-energy x-ray absorptiometry was used to measure LBMD. Estimated glomerular filtration rate (eGFR) was calculated using a modified Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equation for Asians and the CKD-EPI serum creatinine-cystatin c equation. Pearson's correlation analysis and binary logistic regression were used to evaluate associations. Results: The eGFR-ASIA and eGFR-Scys were positively correlated with LBMD ( r  = 0.120 and r  = 0.108, respectively). After adjustments for numerous potential confounders, the odds ratio for participants with LBMD decline in eGFR-ASIA quartile 3 group and 4 group were 2.45 (95% confidence interval [CI] 1.12-5.38, P  < 0.05) and 3.89 (95% CI 1.55-9.76, P  < 0.01), respectively, with P  = 0.003 for the trend in eGFR-ASIA compared with the lowest quartile 1 group of eGFR-ASIA, where the odds ratio of eGFR-Scys for the quartile of 3 and 4 groups were 2.47 (95% CI 1.09-5.62, P  < 0.05) and 2.63 (95% CI 1.10-6.29, P  < 0.05), respectively, with P  = 0.016 for the trend in eGFR-Scys compared with the lowest quartile 1 group of eGFR-Scys . Conclusions: The renal function decline was independently associated with decreased LBMD, and it was possible that the age-related decline in kidney function was an independent risk factor for decreased LBMD in healthy Chinese postmenopausal women.